Emergence of Passiflora caerulea seeds simulating possible natural destinies - Mendiondo, Guillermina M. (2006)
Introduction. The emergence of P. caerulea L. seeds was studied for the first time, in order to obtain useful information for cultivation of this plant with ornamental, edible and medicinal values. Materials and methods. Different treatments (aril removal, mechanical and chemical scarification and combinations of them) were performed on fresh seeds before sowing. The treatments simulated different paths that the seeds may follow in nature in this ornithochorus species, those which small growers could reproduce before cultivation. Seed emergence was recorded periodically for 16 months in a greenhouse. Seed emergence initial time, percentage and speed were calculated. Results and discussion. Seeds immersed in hydrochloric acid (chemical scarification) did not germinate, but the rest of the treatments were successful. Emergence percentages were low in most of the treatments and speed was slow in all of them. The minimum seed emergence initial time was 25 days. The curve of the accumulated number of seeds emerged followed an oscillating sigmoid pattern. Conclusion. It is suspected that dormancy exists, which will be dealt with in another paper.